Protective Immunity Induced by Incorporating Multiple Antigenic Proteins of Toxoplasma gondii Into Influenza Virus-Like Particles - Lee, Su-Hwa; Kang, Hae-Ji; Lee, Dong-Hun; Quan, Fu-Shi (Frontiers in Immunology, 2019)
ABSTRACT Virus-like particle (VLP) as a highly efficient vaccine platform has been used to present single or multiple antigenic proteins. In this study, we generated VLPs (multi-antigen VLPs, TG146) in insect cells co-infected with recombinant baculoviruses presenting IMC, ROP18 and MIC8 of Toxoplasma gondii together with influenza matrix protein 1 (M1) as a core protein. We also generated three VLPs expressing IMC, ROP18, or MIC8 together with M1 for combination VLPs (TG1/TG4/TG6). A total of four kinds of VLPs generated were characterized by TEM. Higher number of VLPs particles per μm2 were observed in multi-antigen VLPs compared to combination VLPs. Mice (BALB/c) were intranasually immunized with multi-antigen VLPs or combination VLPs and challenged with T. gondii tachyzoites (GT1) intraperitoneally. Compared to combination VLPs, multi-antigen VLPs showed significantly higher levels of CD4+ T cell and germinal center B cell responses with reduced apoptosis responses, resulting in significant reduction on parasite burden. These results indicate that higher efficacy of VLPs generated by multi-antigen VLPs can induce significant reduction of parasite burden and better survival of mice than that by combination VLPs, providing important insights into vaccine design strategy for VLPs vaccine expressing multiple antigenic proteins.